Extragenital lichen sclerosus of the breast and silicone breast implants - Alberto Goldman; Uwe Wollina (Our Dermatology Online, 2022)
Lichen sclerosus of the breast (LSB) is an uncommon inflammatory dermatosis of an incompletely understood pathogenesis. Herein, we report the case of a 29-year-old female who developed LSB 23 years after a silicone breast implant. A diagnostic skin biopsy revealed the typical three-layered pathology of an atrophic epidermis with the loss of rete ridges and basal keratinocyte vacuolization, a subepidermal band of sclerosis, and a lichenoid infiltrate of lymphocytes beneath that band. We discuss the possible relationship between silicone breast implants and autoimmune disorders.